Islamic Banking and Green Banking for Sustainable Development: Evidence from Bangladesh - Uddin, Mohammad Nazim; Ahmmed, Monir (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
Green banking is an integral part of Islamic banking that makes a basis of environmental protection. This study attempts to examine the relationship between Islamic banking and green banking that contribute to sustainable development. The study has used the primary data through a structural questionnaire that includes various dimensions on green banking of Islamic banking in Bangladesh. The investigation revealed that Islamic banks had made a significant contribution to green banking that improves the environment as means of cost and energy savings, preservation of natural resources and the need to respect all living things. The study seems to carry an enormous academic value since a few studies have undertaken in this areaDOI: 10.15408/aiq.v10i1.4563